2009
DOI: 10.1007/s10562-009-9919-9
|View full text |Cite
|
Sign up to set email alerts
|

Highly HYD Selective Pd–Pt/support Hydrotreating Catalysts for the High Pressure Desulfurization of DBT Type Molecules

Abstract: A silica-alumina supported Pd-Pt bimetallic catalyst was found to be highly active in dibenzothiophene hydrodesulfurization with preferential selectivity to the hydrogenation (HYD) route of desulfurization at the expense of the direct removal of sulfur. In addition, it was demonstrated that for Pd-Pt catalysts selectivity to HYD can be drastically changed by a ''soft'' change in the nature of the carrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The HDO of DBF reaction over the Pd/COK-12 catalysts was suggested to proceed via the HYD reaction route (Scheme ), which is different from the studies over metal sulfide catalysts, in which both HYD and DDO reaction routes were proposed. , Benzene rings in the DBF were hydrogenated first on the surface of Pd nanoparticles, which could be stable in the mesopores of COK-12. This assumption is consistent with the HDS of DBT over supported Pd catalysts. Aromatic rings being partially or totally hydrogenated were detected in their work, which explained the HYD of DBT in the HDS reaction. Removal of the S atom, followed by the hydrogenation of benzene rings of DBT, was reported.…”
Section: Results and Discussionsupporting
confidence: 83%
“…The HDO of DBF reaction over the Pd/COK-12 catalysts was suggested to proceed via the HYD reaction route (Scheme ), which is different from the studies over metal sulfide catalysts, in which both HYD and DDO reaction routes were proposed. , Benzene rings in the DBF were hydrogenated first on the surface of Pd nanoparticles, which could be stable in the mesopores of COK-12. This assumption is consistent with the HDS of DBT over supported Pd catalysts. Aromatic rings being partially or totally hydrogenated were detected in their work, which explained the HYD of DBT in the HDS reaction. Removal of the S atom, followed by the hydrogenation of benzene rings of DBT, was reported.…”
Section: Results and Discussionsupporting
confidence: 83%
“…Catalytic tests . Catalytic tests were carried out in a Catatest provided with a high‐pressure fixed‐bed continuous flow reactor [23–25,27,29,52,173] . The reactor was packed with the catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…Catalytic tests were carried out in a Catatest provided with a high-pressure fixed-bed continuous flow reactor. [23][24][25]27,29,52,173] The reactor was packed with the catalyst. Prior to the latter, the catalytic powders were pelletized, ground, and sieved to obtain particles with diameters ranging from 300 to 600 μm.…”
Section: Determination Of the Distribution Of Surface Hydroxyls Protonmentioning
confidence: 99%
“…Mechanistically, it is well-known that 4,6-DMDBT is desulfurized by either a hydrogenation (HYD) route or a direct desulfurization (DDS) route [4,18]. A group of researches [15,[19][20][21][22][23][24][25] proposed that 4,6-DMDBT is adsorbed following π and σ adsorptions: in the former, the aromatic ring of the 4,6-DMDBT is adsorbed on the active site, whereas in the latter the sulfur heteroatom is the one being adsorbed on. It suggests that HYD route involves both π and σ adsorptions while the DSD route involves only σ adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al [31], Yoshimura et al [22] and Chen et al [28] observed that Pd in a Pt-Pd/γ-Al 2 O 3 catalyst leads to inhibit Pt agglomeration on the catalyst surface, increasing its hydrogenation activity and its resistance to be deactivated by surface sulfur. Baldovino-Medrano et al [24] evaluated a silica-alumina supported Pt-Pd catalyst, observing that this bimetallic catalyst is highly active in dibenzothiophene hydrodesulfurization with preferential selectivity to HYD route. Núñez et al [32] realized oxidereduction studies for Pt-Pd/TiO 2 and Pt-Pd/γ-Al 2 O 3 -TiO 2 catalytic systems during the hydrogenation of biphenyl and the HDS of 4,6-DMDBT.…”
Section: Introductionmentioning
confidence: 99%